Biocompatibility of experimental Ti-30Ta implants with compromised primary stability: effect of TEA - Rezende, Maria Cristina Rosifini Alves [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; de Oliveira, João Augusto Guedes; Claro, Ana Paula Rosifini Alves [UNESP] (Elsevier, 2013)
Purpose: Ti-Ta alloys have high potential for dental application due to a good balance between high strength and low modulus. Absence of primary anchoring may occur when dental implants are installed immediately after tooth extraction. Tranexamic acid (TEA) is used to reduce fibrin degradation and can prevent early blood clot breakdown. The aim of this study was to evaluate the biocompatibility of Ti-30Ta implants associated or not with tranexamic acid and installed with compromised primary stability. Methods and materials: Fabricated were 20 implants of titanium ASTM F67 (Grade 4) and 20 implants of Ti-30Ta alloy with dimensions of 2.1 mm × 2.8 mm Ø. They were divided (n = 10) into Group I (Ti machined), Group II (Ti machined/tranexamic acid), Group III (Ti-30Ta alloy) and Group IV (Ti-30Ta/tranexamic acid) and were implanted in tibia (defects with 2.5 mm × 3.2 mm Ø) of 40 male rats (250 g). The surgical sites were rinsed with 5% tranexamic acid solution in Groups II and IV. The animals were euthanized at 45 days postoperative. The pieces were processed in methyl methacrylate (Stevenel's blue/Alizarin red). The percentage of peri-implant tissue repair was analyzed via images obtained by an optical microscope coupled to a digital camera using Leica software and Adobe Photoshop QWin. Data were analyzed statistically with a significance level of 5%. Results: Histomorphometric results showed 97.16% of bone-implant contact for group IV, 89.78% of bone contact for group III, 70.89% for group II and 61.59% of bone contact for group I. The statistical analyses demonstrated significant differences (P < 0.05) among group I and other groups. Conclusion: The results suggest that (a) Ti-30Ta promoted an increase of bone healing and apposition around implant; (b) tranexamic acid favored the stabilization of blood clot and bone formation.
Keywords: Titanium; Osseointegration; Tranexamic acid